Pencegahan Covid 19 RW 2 & 3 Desa Kenteng Sempor Dengan Teori Keperawatan Betty Neument Menggunakan CAP - Marsito Marsito; Rina Saraswati; Sarwono Sarwono; Ernawati Ernawati; Mustoleh Mustoleh (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The total population of Kenteng Village is 4680 people, of which in the 02 and 03 pillarsthere are 1048 people (22.39%) of the 7 community units. Given the high mobility andstill in a state of the COVID-19 pandemic, it is necessary to look at preventing the spreadof Covid. Seeing these results, the researchers used Betty Neuman's nursing theory withthe Community as Partner approach. With the aim of looking at core data on age, safetyand transportation such as wearing masks, maintaining distance, and washing hands forhealth services that have been vaccinated against Covid 19. The sample is all residents ofthe 02 and 03 Kenteng Village Community Units totaling 1048 people. From the resultsof the core data study, it was found that the majority of people aged over 18 years were798 people (88.5%), safety and transportation using masks were sometimes used by 507people (48%), doing hand washing sometimes there were 665 people (58). %) and keepinga distance the result is never keeping a distance there are 604 people (58%). The numberof people who have been vaccinated is 735 people (70.1%). That Betty Neuman's Nursingtheory uses the Community as Partner approach in community nursing to see how toprevent covid 19. Thus, Betty Neuman's nursing theory can be used in the prevention ofCovid 19 in the community.